1982
DOI: 10.1172/jci110699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Iodothyronine 5′-Deiodinase and Other Thyroid-Hormone-dependent Enzyme Activities in the Cerebral Cortex of Hypothyroid Neonatal Rat

Abstract: A B S T R A C T Recent studies have shown that -75% of the nuclear 3,5,3'-triiodothyronine (T3) present in adult rat cerebral cortex (Cx) derives from 5'-deiodination of thyroxine (T4) within this tissue. The activity of iodothyronine 5'-deiodinase (I 5'D), the enzyme catalyzing T4 to T3 conversion, increases rapidly after thyroidectomy, suggesting that this could be a compensatory response to hypothyroxinemia. To evaluate this possibility during the period of central nervous system maturation, we studied seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
3

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 38 publications
5
52
1
3
Order By: Relevance
“…a-Glycerophosphate dehydrogenase (a-GPD) was measured as described earlier (30)(31)(32)(33) and serum T4 and T3 by radioimmunoassay (33).…”
Section: Methodsmentioning
confidence: 99%
“…a-Glycerophosphate dehydrogenase (a-GPD) was measured as described earlier (30)(31)(32)(33) and serum T4 and T3 by radioimmunoassay (33).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is well documented that, in hyperthyroid states, type-2 deiodinase (D2) activity is decreased in pituitary, central nervous system, and brown adipose tissue (Bates et al 1999, Schneider et al 2001, Volpato & Nunes 2001. Moreover, in the early postnatal life, changes in the expression of TH receptor isoforms are taking place, under TH control (Kaplan & Yaskoski 1981, Silva & Larsen 1982, Bradley et al 1992, Santini et al 1999, which interferes with the pattern of GH gene response to T3 observed in adult rats, in which the adult isoforms predominate. Furthermore, in the NP, the a-2 isoform of TR (TRa 2) is highly expressed, which prevents, in a certain degree, the binding of other TR isoforms (TRa 1, b1, and b2) to the DNA-binding domain (DBD) of the T3 target genes (Bradley et al 1992), and taking into account that T3-binding domain is missing in the TRa 2, this might prevent, in some way, the impact of TH on the expression of many genes in this period of development, in which the patterns of gene expression that will persist in adult life is being settled (Csaba & Nagy 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The 5'DII deiodinating system predominates in brain (33), brown adipose tissue (34), and homogenates of the chorionic membrane decidua of the placenta (35). The enhancement of this system in the case of low serum T4 values may explain the high local T3 production found in the cortex and cerebellum of newborn rats with HT (36,37). Otherwise, the 5'DI system, more prevalent in liver, kidney, and muscle (38), is depressed in HT (36).…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of this system in the case of low serum T4 values may explain the high local T3 production found in the cortex and cerebellum of newborn rats with HT (36,37). Otherwise, the 5'DI system, more prevalent in liver, kidney, and muscle (38), is depressed in HT (36). If bone tissue like muscle tissue (38) belongs to the 5'DI compartment, it will be dependent on circulating T3 for its metabolism and maturation (37).…”
Section: Discussionmentioning
confidence: 99%